Liver stiffness reduction and serum fibrosis score improvement in HIV/hepatitis C virus‐coinfected patients treated with direct‐acting antivirals. Issue 8 (28th June 2018) - Fabbri, G; Mastrorosa, I; Vergori, A; Timelli, L; Lorenzini, P; Zaccarelli, M; Cicalini, S; Bellagamba, R; Plazzi, MM; Mazzotta, V; Antinori, A; Ammassari, A
Abstract : Objectives: Only a few studies have addressed liver stiffness dynamics after hepatitis C virus (HCV) treatment in patients with HIV/HCV coinfection. The aim was to evaluate the variation in liver stiffness and in serum liver fibrosis scores in HIV/HCV‐coinfected patients before and after treatment with direct‐acting antivirals (DAAs). Methods: Liver stiffness measured using transient elastography as well as serum liver fibrosis scores [fibrosis‐4 (FIB‐4) score and the aspartate aminotransferase to platelet ratio index (APRI)] were evaluated before and at 6–12 months after DAA treatment. Variation in the outcome variables was evaluated using the Wilcoxon nonparametric test. Univariate analysis and multivariate regression models were used. Results: A total of 78 HIV/HCV‐coinfected subjects were included in the study. Median values of hepatic stiffness significantly decreased after DAA treatment compared with baseline [16.8 (interquartile range (IQR) 10.2–27.0) kPa at baseline vs . 9.4 (IQR 6.7–15.0) kPa after DAA treatment; P < 0.01). Further, a decrease in median FIB‐4 score [2.8 (IQR 1.5–4.8) vs . 2.0 (IQR 1.3–3.2), respectively; P < 0.01] and APRI [0.9 (IQR 0.5–2.2) vs . 0.4 (IQR 0.2–0.7), respectively; P < 0.01] was found. In univariate analysis, liver stiffness decrease was associated with increasing age, 'other' HCV genotype ( vs . G1), the presence of cirrhosis, higher pre‐DAA liver stiffness, sofosbuvir‐based regimens and longer DAA treatment (all P < 0.05). Multivariate regression confirmed the significance of the association only with higher baseline liver stiffness ( P < 0.01). Greater FIB‐4 and APRI reductions were associated with higher respective baseline values, while the presence of hepatic steatosis correlated with lower score reduction after DAA. Conclusions: A reduction in liver stiffness and an improvement in fibrosis scores were observed in HIV/HCV‐coinfected patients soon after DAA treatment. The clinical implications of these observations need to be evaluated in larger populations with longer follow‐up.